THE INFLUENCE PROJECT BASED LEARNING MODEL ASSISTED BY ANIMATED VIDEO ON INCREASING MOTIVATION AND LEARNING OUTCOMES FOR CLASS XI HIGH SCHOOL CHEMISTRY ON COLLOID MATERIALS - Sibarani, Nancy Agalalis; Riris, Ida Duma (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2025)
This study aims to determine the effect of using the Project Based Learning model on student learning motivation, increasing student learning outcomes on colloidal material, knowing the correlation between motivation and student learning outcomes and knowing the increase in student learning outcomes with the Project Based Learning model assisted by animated media on colloidal material. To achieve these objectives, the Project Based Learning model was used. The research instruments used were tests and non-tests. The results showed that there was an effect of using the project-based learning model assisted by animated media on student motivation in colloidal material with a large tcount of 19.01. There is an effect of using the project-based learning model assisted by aimasi media on improving student learning outcomes with a tcount of 6.59. There is a positive correlation between student motivation and the improvement of learning outcomes taught using the project-based learning model assisted by animated media on colloidal material with a large r count of 0.56 and the effect of motivation on student learning outcomes of 31.3%. There is an increase in student learning outcomes with the Project Based Learning model assisted by animated media on colloidal material with an average increase from 32.96 to 82.96 and obtained a gain value of 0.743 or 74.3% with a high category.